Angiotensin II Causes Biphasic STAT3 Activation Through TLR4 to Initiate Cardiac Remodeling. Issue 6 (December 2018) - Han, Jibo; Ye, Shiju; Zou, Chunpeng; Chen, Taiwei; Wang, Jingying; Li, Jieli; Jiang, Liqin; Xu, Jianjiang; Huang, Weijian; Wang, Yi; Liang, Guang
Abstract : Evidence indicates that Ang II (angiotensin II) activates STAT3 (signal transducer and activator of transcription 3) in cardiomyocytes. However, the mechanisms underlying STAT3 activation and downstream responses are not fully known. In this study, we show that Ang II caused biphasic STAT3 activation in cardiomyocytes. A rapid and early activation was mediated by direct association between TLR4 (toll-like receptor-4) and STAT3. This early activation increased IL-6 (interleukin-6) production, which in turn, induced the second STAT3 activation through the IL-6/gp130 (glycoprotein 130)/JAK2 (Janus-family tyrosine kinases 2) pathway, resulting in unregulated expression of genes for cardiac remodeling. Moreover, STAT3 inhibition or TLR4 knockout in mice protected against Ang II–induced hypertrophy, fibrosis, and cardiac functional deficits. Thus, Ang II–induced STAT3 activation in cardiomyocytes was biphasic, providing a sequential induction of IL-6 and myocardial remodeling genes, respectively. This work supports a novel mechanism on STAT3 activation in Ang II–induced cardiac dysfunction and remodeling. Abstract : Supplemental Digital Content is available in the text.